Tres estrategias para la participación de públicos y no públicos en el proceso de renovación del Museo del Oro Zenú en Cartagena - Campuzano Botero, Juliana (Boletín Museo del Oro, 2021)
Este artículo muestra el planteamiento, diseño, desarrollo, sistematización y resultados de tres actividades participativas realizadas en distintos lugares de Cartagena dentro del proceso de renovación del Museo del Oro Zenú. Las actividades surgieron como una propuesta de acercamiento entre el museo y la ciudadanía, con el fin de conocer las necesidades, opiniones y expectativas de los habitantes de la ciudad respecto del museo. Se llevaron a cabo en el parque Bolívar, centro histórico de Cartagena; en una finca a las afueras de la ciudad, con la comunidad zenú del cabildo indígena de Membrillal, y en el sector La Islita del barrio El Pozón. Three strategies for public and non-public participation in the Zenú Gold Museum renovation process Abstract: This article illustrates the proposal for, and the design, development, analysis and results of, three participative activities carried out in different parts of Cartagena as part of the Zenú Gold Museum renovation process. The activities were devised as a way to bring the museum closer to local people and to discover the needs, opinions and expectations of the city’s inhabitants with respect to the museum. The activities were carried out in Bolívar Park, in Cartagena’s historic centre, on a farm on the outskirts of the city, with the Zenú community in the indigenous Membrillal reserve, and in the La Islita sector of El Pozón neighbourhood. Key words: Zenú Gold Museum, participation, Cartagena, publics, communities